(untitled) (Czech Journal of International Relations, 2002)
Organised crime (OC) from the Middle East, sometimes called ’Arab Organised Crime’, does not attract as much attention as Chinese, Italian or Russian OC. However, especially in the context of illegal migration, illegal trade in drugs and terrorism, it is going to be a very significant security issue. The Czech Republic has become one of the crossroads of Arab organised crime in Europe. Many ethnic Arabs permanently lived in the former Czechoslovakia before 1989 because of the former communist regime’s good relations with the Arab countries. Some of these persons holding Czech citizenships created cells of Arab OC groups which have penetrated the CR since the beginning of the 1990s. The Arabs are engaged in marijuana and hashish smuggling from Northern Africa and Central Asia-and in the last 2 to 3 years in the heroin trade as well. They are active in the weapons trade, illegal migration and financial fraud. The Czech Arab underworld has contacts with fundamentalist and terrorist organisations such as the Algerian FIS, GIA, Palestinian Liberation Front, Hezbollah and Al Fatah. Increasing activity was registered in connection with the start of Radio Free Europe’s broadcast from the CR to Iran and Iraq. The article defines the role of the CR in the Arab international criminal networks, estimates future trends in the development of the Czech criminal underworld and the impact of the Arab OC activities on the Czech economy and society.